2020
DOI: 10.1186/s40885-020-00149-9
|View full text |Cite
|
Sign up to set email alerts
|

Family history of chronic illness, preterm gestational age and smoking exposure before pregnancy increases the probability of preeclampsia in Omo district in southern Ethiopia: a case-control study

Abstract: Background: Preeclampsia is a complex syndrome that is considered a disorder specific to pregnancy. However, research indicates that diffuse maternal endothelial damage may persist after childbirth. On the other hand, women who had a history of pre-eclampsia are at an increased risk of vascular disease. Considering that the multifactorial nature of pre-eclampsia in a remote health setting, knowledge of risk factors of preeclampsia gives epidemiological significance specific to the study area. Therefore, this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 87 publications
0
5
0
1
Order By: Relevance
“…10 But it was in agreement with two studies results, which found a significant increase of CS among PE females when compared to females without PE. 12,13 Current study reported that there was a significant decrease of GA at delivery among females with PE. Preeclampsia could be early preterm onset when diagnosed before 34 week gestation, late preterm onset if diagnosed from 34 to 37 weeks, and term onset when diagnosed at or beyond 37 weeks.…”
Section: Resultsmentioning
confidence: 96%
“…10 But it was in agreement with two studies results, which found a significant increase of CS among PE females when compared to females without PE. 12,13 Current study reported that there was a significant decrease of GA at delivery among females with PE. Preeclampsia could be early preterm onset when diagnosed before 34 week gestation, late preterm onset if diagnosed from 34 to 37 weeks, and term onset when diagnosed at or beyond 37 weeks.…”
Section: Resultsmentioning
confidence: 96%
“…The discrepancies between the studies could be attributed to differences in clinical methodology, sizes of the studied groups, risk of the studied populations, the numbers of early-onset preeclampsia (PE) (<34th weeks) and late-onset PE cases, ethnic differences, as well as differences in the definitions of ‘family hypertension’ or ‘hypertension in pregnancy’ and the degree of adjustment [ 4 , 8 , 11 , 12 , 13 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This disease, which is characteristic of pregnancy, develops de novo after 20 weeks of gestation and includes gestational hypertension (GH) and preeclampsia (PE) as well as PE superimposed on chronic hypertension [ 2 ]. PIH affects an average of 10% of pregnant women, although in some regions of the world this percentage is much higher [ 1 , 3 , 4 ]. Preeclampsia (PE) (in which high blood pressure is accompanied by particular organ disorders) occurs on average in 2–5% of pregnancies [ 2 ] but is seven times more common in developing than in developed countries [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations